Pengaruh Model PBL Terhadap Kemampuan Literasi Siswa pada Materi Keberagaman Budaya Indonesia - Mawadah, Atik Nur; Kusumaningsih, Widya; Paryuni (Jurnal Penelitian Multidisiplin Ilmu, 2024)
This study aims to determine the effect of Problem Based Learning model on the material of Indonesian cultural diversity on literacy skills of Gajahmungkur 04 State Elementary School in Semarang City. This study used experimental research (Pre experiment Design) design one group pretest-posttest. The sample used was grade V students of Gajahmungkur 04 State Elementary School which amounted to 26 people. The instrument used to collect data is a test. The data analysis technique uses quantitative analysis by conducting paired sample tests. The prerequisite test uses a normality test with a significant value of 0.243> 0.05. So it can be interpreted that the data is normally distributed. The results showed that the paired sample t-test value was 21.779> 1.711 (t_hitung> t_tabel), so it can be concluded that the application of the problem-based learning model has a significant effect on the literacy skills of fifth grade students of Gajahmungkur 04 State Elementary School. Translated with DeepL.com (free version)